Bacterial diversity of Elephant Dung using 16S rRNA gene sequence analysis - Tan Shan Wen (2019)
The objective of this study was to identify the bacterial diversity of dung from Asian elephant (Elephas maximus). The important uses of elephant dung have been identified through various studies, but the knowledge for the bacterial diversity of elephant dung is very limited and insufficient. In this study, 16S rRNA gene sequence was used to identify the bacterial distribution and diversity of elephant dung. Thirteen pure bacterial isolates labelled as ED1, ED2, ED3, ED4, ED5, ED6, ED7, ED8, ED9, ED10, ED11, ED12, and ED13 were obtained and basic characterisation of bacteria by Gram staining was performed. Polymerase Chain Reaction (PCR) of the bacteria isolates was done by targeting 16S rRNA gene. Unpurified Polymerase Chain Reaction (PCR) products of ED2, ED5 and ED7 were sent for purification and sequencing. The obtained sequences were compared with the sequences available in GenBank database. BLAST was used to perform identification of bacteria based on the percentage of similarity. Phylogenetic analysis was done by constructing a phylogenetic tree by using Neighbor-Joining (NJ) method. The obtained sequences were BLAST and the results of their phylogenetic analysis showed that ED2 has 90% similarity with Exiguobacterium profundum, ED5 has 98% similarity with Flavobacterium lutescens, and ED7 has 99% similarity with Micrococcus luteus. Micrococcus luteus is cellulolytic bacteria which can produce cellulose enzyme to degrade the cellulose found in plant cell wall. The results obtained from this study provided a preliminary result and further studies of elephant dung is needed to be done for more understanding of microbial diversity of elephant dung. The findings of this study focus on determining the ecological significance of bacteria found in elephant dung.